STUDENTS’ SPIRITUALITY CRISIS IN THE DIGITAL ERA: A CRITICAL REVIEW OF THE DOMINANCE OF COGNITIVE APPROACHES IN ISLAMIC RELIGIOUS EDUCATION LEARNING: Krisis Spiritualitas Siswa di Era Digital: Telaah Kritis terhadap Dominasi Pendekatan Kognitif dalam Pembelajaran PAI - Yoga Mahath Pandika (SOSIOEDUKASI, 2026)
This article examines the crisis of student spirituality in the digital era through a critical reading of cognitive dominance in Islamic Religious Education learning. The study was compiled from the fact that increasing access to religious knowledge does not always go hand in hand with the formation of students’ inner awareness. The research uses a qualitative study based on literature studies with a critical conceptual analysis of the works of Paulo Freire, Thomas Lickona, and Al-Ghazali, accompanied by journal articles that discuss religious learning, character education, critical pedagogy, and student spirituality. The analysis was carried out through the identification of theoretical categories, comparative reading of the latest literature, and then interpretive synthesis. The results of the study show that the dominance of learning based on material mastery produces inequality between moral knowing, moral feeling, and moral action. Students know religious values verbally, but affective attachment to these values develops unevenly. The digital space expands access to religious materials, but knowledge is often received in fragments. Freire pointed out that one-way learning relationships still persist in religious learning. Lickona explained that moral knowledge has not automatically turned into moral action. Al-Ghazali emphasized that knowledge must move to the territory of tazkiyat al-nafs. This article offers a synthesis of reflective pedagogy as a direction for the renewal of religious learning.